2019
DOI: 10.1177/2158244019865803
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Factors Impelling the Adoption of e-Health: A Perspective of African Expats in China

Abstract: The purpose of the study was to analyze the factors affecting the acceptance and adoption of e-Health applications among African expats in China from the patient’s perspective. This research used extended technology acceptance model (TAM) with the addition of privacy and trust. The survey method with the structured questionnaire was used to collect data from more than 300 African expats in three Tier 1 cities of China. Hypotheses were tested using partial least squares (PLS) method, a structural equation model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
24
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 80 publications
(88 reference statements)
6
24
2
3
Order By: Relevance
“…In this regard, the implementation of new technologies usually faces obstacles to their final acceptance by users, as is the case of e-heath technologies in some countries. [30][31][32] In relation to these observations, it is convenient to mention that in addition to the availability of technologies, the will and motivation of people is important for the adoption of e-health systems. 29 In our opinion, the lack of motivation to adopt e-health services is associated with cultural and social aspects of the Arab people.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the implementation of new technologies usually faces obstacles to their final acceptance by users, as is the case of e-heath technologies in some countries. [30][31][32] In relation to these observations, it is convenient to mention that in addition to the availability of technologies, the will and motivation of people is important for the adoption of e-health systems. 29 In our opinion, the lack of motivation to adopt e-health services is associated with cultural and social aspects of the Arab people.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, internet search behavior that indicates the health literacy of an individual influences internet usage for health purposes. Additionally, other studies found that the use of the internet for health is subjective to factors including social inspirations (M. Khasawneh, Nusair, Arabyat, Karasneh, & Al-Azzam, 2021), access to internet facilities Khan, Xitong, Ahmad, & Shahzad, 2019) and personal enthusiasm (Yuan et al, 2015). Besides this, numerous researchers concluded significant influence of perceived health information on the internet regarding the use of the internet for health (Boland, Juntunen, Kim, Adams, & Navarro, 2019;Dahleez, Bader, & Aboramadan, 2020;Yu et al, 2021).…”
Section: Introduction and Background Of The Studymentioning
confidence: 99%
“…[33][34][35][36] Some studies showed that the main elements of TAM perceived usefulness, perceived ease of use, and attitude towards eHealth technology have a strong impact on a user's intention to use eHealth technology. 9,35,37,38 Besides the main constructs of TAM other external variables like information sharing, the staff's IT experience, and technical infrastructure was found positively significant to the intention of eHealth technology. 28,39 However, there is still inadequate information on how technologies are adopted and used in Healthcare by health professionals, particularly in a resource-limited context.…”
Section: Introductionmentioning
confidence: 99%